Efficacy and safety of 11 oral preparations of single-source traditional Chinese medicines in the treatment of unstable angina pectoris: a systematic review and network meta-analysis - Li, Xiuchong; Li, Xiaohui; Zhu, Xing; Xin, Xin; Sheng, Ran; Wang, Te; Kan, Junming; Huang, Yongsheng (Frontiers in Pharmacology, 2025)
BackgroundUnstable angina pectoris (UAP) is a cardiovascular disease with high morbidity and can cause serious cardiovascular complications. Oral preparations of single-source traditional Chinese medicines (SSTCM-OPs) are increasingly used as adjuncts to conventional treatments (CT) for UAP, providing complementary therapeutic advantages with favorable safety profiles. However, the comparative efficacy and safety of these SSTCM-OPs remain unclear. This network meta-analysis (NMA) evaluates the efficacy and safety of 11 approved SSTCM-OPs to guide clinical practice in UAP treatment.MethodsA comprehensive literature search was conducted across eight databases: China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), Wanfang Database, China Biomedical Literature Database (CBM), Web of Science, PubMed, EMBASE, and the Cochrane Library. Only randomized controlled trials (RCTs) examining SSTCM-OPs combined with CT for UAP were included. The search covered publications up to 4 December 2024. Quality assessment was performed using RevMan 5.4.1, and certainty of evidence was evaluated with GRADEpro software 3.6.1. A frequentist random-effects model was employed for NMA. Statistical analysis was performed using Stata 18.0.ResultsA total of 72 RCTs involving 11 SSTCM-OPs and 7,360 patients were included. The NMA results demonstrated that Maixuekang oral preparation combined with CT and Xinyue oral preparation combined with CT showed superiority in terms of angina efficacy; Xindakang oral preparation combined with CT and Yinxingtongzhi oral preparation combined with CT showed superiority in terms of Electrocardiogram (ECG) efficacy and had an advantage in reducing nitroglycerin dosages; Xindakang oral preparation combined with CT and Yinxingtongzhi oral preparation combined with CT showed superiority in reducing nitroglycerin dosages; Zhenyuan oral preparation combined with CT and Diaoxinxuekang oral preparation combined with CT showed superiority in reducing frequency of angina; Xinnaoshutong oral preparation combined with CT and Yinxingtongzhi oral preparation combined with CT showed superiority in reducing duration of angina; Xuezhikang oral preparation combined with CT showed superiority in improving TC, LDL-C, and HDL-C levels as well as reducing the occurrence of MACEs; Yinxingtongzhi oral preparation combined with CT showed superiority in improving TG and PV levels; Lastly, Xuesaitong oral preparation combined with CT and Yinxingye oral preparation showed superiority in reducing hs-CRP levels.ConclusionAll 11 SSTCM-OPs combined with CT showed advantages over CT alone in treating UAP. Notably, Xinnaoshutong + CT did not significantly reduce angina frequency, but it was effective in other outcomes. These findings suggest incorporating traditional Chinese medicine into standardized treatment regimens may enhance UAP management.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024618094.